HUMAN SYSTEM INTER IN MANAGE INFORMATION SYSTEM : IMPLICATIO FOR DECISION EFFECTIVENESS - Dwi Sembe Sigita; Setyaasih; Harjo Lukito; Risa Amalia Muzrifah; Adhis Helsa Aurellia (MANAJEMEN DEWANTARA, 2026)
Objective: This study aims to explore the impact of Human System Interaction (HSI) on Decision Making Effectiveness within Management Information Systems (MIS). It seeks to understand how system usability, interface design, and user engagement influence the quality and efficiency of decisions made through MIS. Research Method: A quantitative research design was employed, utilizing a survey of 200 MIS users across different sectors. Data was gathered using a Likert scale questionnaire to measure HSI and Decision-Making Effectiveness. The relationship between these variables was analyzed through regression analysis and Structural Equation Modeling (SEM) to evaluate the strength and significance of HSI in improving decision outcomes. Results: The study found a significant positive relationship between HSI and Decision-Making Effectiveness, with HSI explaining 60% of the variance in decision quality (β = 0.78, p < 0.01). Participants who rated the system higher in terms of usability and design were more likely to report better decision-making. These findings emphasize the critical role of user centered system design in enhancing decision quality within organizations.